2016
DOI: 10.1111/risa.12583
|View full text |Cite
|
Sign up to set email alerts
|

Failing to Fix What is Found: Risk Accommodation in the Oil and Gas Industry

Abstract: The present program of research synthesizes the findings from three studies in line with two goals. First, the present research explores how the oil and gas industry is performing at risk mitigation in terms of finding and fixing errors when they occur. Second, the present research explores what factors in the work environment relate to a risk-accommodating environment. Study 1 presents a descriptive evaluation of high-consequence incidents at 34 oil and gas companies over a 12-month period (N = 873), especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Process is one of the best researched areas of learning from incidents, with at least one research backed questionnaire available to assess areas of weakness (Littlejohn et al, 2017). However, one of the most important areas that is often overlooked is the implementation of actions (Stackhouse & Stewart, 2016). Lundberg et al (2010) documented in his interviews with accident investigators that the actions recommended for implementation are often influenced by many factors, such as what is technically possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Process is one of the best researched areas of learning from incidents, with at least one research backed questionnaire available to assess areas of weakness (Littlejohn et al, 2017). However, one of the most important areas that is often overlooked is the implementation of actions (Stackhouse & Stewart, 2016). Lundberg et al (2010) documented in his interviews with accident investigators that the actions recommended for implementation are often influenced by many factors, such as what is technically possible.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown limited use of aggregated data, and inconsistencies in implementing recommended actions (Lundberg, Rollenhagen, & Hollnagel, 2010;Lundberg, Rollenhagen, Hollnagel, & Rankin, 2012;Stackhouse & Stewart, 2016). Key to ensuring that these steps are actually carried out are detailing these phases of the LFI process in documentation, including clear indication of responsibility (Drupsteen et al, 2013;Lundberg, Rollenhagen, & Hollnagel, 2009).…”
Section: Processmentioning
confidence: 99%
“…Many causes can lead to such events, as indicated by Chang and Lin [12], such as operational errors (e.g., oil leaks due to operational errors, drain valves left open accidentally, overfill, high inlet temperature, and vent closed during loading), maintenance errors (e.g., sparks, welding, poor grounding of soldering equipment, and circuit shortcut), tank cracks/ruptures (e.g., corrosion, high-pressure liquid from downstream vessels moving back up, poor fabrication, and poor soldering), equipment/instrument failure (e.g., thermostat failure, relief valves failure, heater failure, sunk, floating roof, level indicator, and discharge valve rupture), lightning (e.g., rim seal leaks, poor grounding, and flammable liquid leak from seal), and piping ruptures/leaks (e.g., pump leak and cut accidentally by a contractor), among others. This can be considered, i.e., how the oil and gas industry performs risk mitigation: finding and fixing errors when they occur, and exploring what factors in the work environment relate to a risk-accommodating environment [22].…”
Section: Hazard Identification Proceduresmentioning
confidence: 99%
“…Sustainability 2021, 13, x FOR PEER REVIEW 5 of 21 corrosion, high-pressure liquid from downstream vessels moving back up, poor fabrication, and poor soldering), equipment/instrument failure (e.g., thermostat failure, relief valves failure, heater failure, sunk, floating roof, level indicator, and discharge valve rupture), lightning (e.g., rim seal leaks, poor grounding, and flammable liquid leak from seal), and piping ruptures/leaks (e.g., pump leak and cut accidentally by a contractor), among others. This can be considered, i.e., how the oil and gas industry performs risk mitigation: finding and fixing errors when they occur, and exploring what factors in the work environment relate to a risk-accommodating environment [22].…”
Section: Hazard Identification Proceduresmentioning
confidence: 99%